Pengaruh Puja Bakti Terhadap Kecerdasan Spiritual Siswa Agama Buddha - Bawono, Budhi; Nyanasuryanadi, Partono; Prasetyo, Eko (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
This article covers aspects of prayer in the development of spiritual intelligence. The study aims to investigate the impact of the practice of puja bakti on the spiritual intelligence of Buddhist students at Bhakti Karya Kaloran High School. The study involved research subjects such as Buddhist religious students at Bakti Karya Kaloran High School in 2023 who were selected as samples of research. The research method used is a quantitative method with a correlational approach. The correlation value between the variable puja bakti to spiritual intelligence is 0.712. This value can be predicted that the relationship of the two variables tested is in the strong category. The results of the study showed a significant correlational relationship between the performance of bakti puja and the spiritual intelligence of students with evidence of a significance value of 0.003 < 0.05 and a t-count value of 6.251 > t-table 2,021, also contributing 49.6%. The recommendation from this study is to implement morning prayer routine and targeted in the school environment to enhance the spiritual intelligence of students.